2020
DOI: 10.3390/su12208364
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Individual Motivations and Social Capital on the Continuous Usage Intention of Mobile Social Apps

Abstract: Mobile social apps have experienced enormous growth as online personal networking media. Social exchange theory (for individual motivation), theories of collective action and social capital theory (for social capital) can be applied in order to understand how an individual’s behavior may exert effects on or receive influences from other users with regard to the continuance usage intention of mobile social apps. This study examines individual motivations and social capital affecting relationship quality in term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 122 publications
(143 reference statements)
0
11
0
Order By: Relevance
“…Research has described flow encounters in various pursuits, including reading, dancing, rock climbing, chess, etc. Provided the reduced figures of returning users, studies that examine the crucial issues that affect continuance use intent are vital to individuals who formulate marketing tactics for online platforms ( Lee and Kim, 2020 ). The sustainable use of online platforms in business processes is critical to generating commercial value.…”
Section: Introductionmentioning
confidence: 99%
“…Research has described flow encounters in various pursuits, including reading, dancing, rock climbing, chess, etc. Provided the reduced figures of returning users, studies that examine the crucial issues that affect continuance use intent are vital to individuals who formulate marketing tactics for online platforms ( Lee and Kim, 2020 ). The sustainable use of online platforms in business processes is critical to generating commercial value.…”
Section: Introductionmentioning
confidence: 99%
“…While precision and completeness have been well suggested in previous studies, value innovation and social impact have been studied less. Value innovation can be an attribute based on how much BDA obtains meaningfulness, value added, and relevance from BDA, which have been suggested in previous studies [63,64] . Social impact can be explained in terms of alignment and relevance in the social context of BDA as data quality attributes.…”
Section: Research Modelmentioning
confidence: 99%
“…Predictability is the extent to which it is possible to predict phenomena and provide meaning and insights in relation to them. Interpretability is the extent to which it is possible to interpret relationships among specific events, objects, and groups [64] . In a similar vein, Feki and Mnif [63] suggested meaningfulness as a data quality dimension.…”
Section: Value Innovation In Bda and Decision-making Performancementioning
confidence: 99%
“…However, the attitudes toward information technology may be confusing because the empirical studies on attitudes toward information technology have multiple assumptions. For example, some empirical studies removed attitudes from the TAM [ 40 , 41 , 42 ], and other studies have expanded the attitude effect on continuance intention [ 43 , 44 ] and purchase intention [ 45 , 46 , 47 ]. In summary, it is crucial to clarify the conditions under which attitude factors can link cognition, emotion, and intention.…”
Section: Evaluation Proceduresmentioning
confidence: 99%
“…Although attitudes toward information technology are connected to information technology adoption intention, many recent studies have suggested that attitudes toward information technology are an antecedent of continuance intention [ 43 , 44 ]. Indeed, an individual’s attitude toward a certain object can be fostered by their individual experience, which is similar to a continuing desire, preference, and identity, and is likely to form loyalty [ 49 , 50 ].…”
Section: Evaluation Proceduresmentioning
confidence: 99%